History of Ancient Greece in fifty lives - Stuttard, David, ....- (London : Thames & Hudson, 2014)
The political leaders, writers, artists and philosophers of ancient Greece turned a few city states into a pan-Mediterranean civilization. But who were these people, what do we know of their lives and how did they interact with one another? This highly readable, original new approach to telling the history of Greece weaves together the lives of the movers and shakers of the Greek world into a continuous narrative up until the rise of Rome. From mathematics to politics, from painting and sculpture to sport, the reader will meet both the famous and less well-known figures such as Milo, the Olympic wrestler; Aspasia, the brilliant female intellectual; Zeuxis, the painter who invented trompe l'oeil; and Epaminondas, who taught tactics to Philip of Macedon. David Stuttard has written numerous books on the Classical world including 'The Parthenon: Power and Politics on the Acropolis'. Recensie(s) The real power of the book is the author's ability to convey the context of the subjects' lives and the interconnected effect of their actions on their society and one another. A highly enjoyable and accessible volume. For readers new to Greek history, it provides an excellent overview of significant events and personages, while those familiar with its subjects might find that the presentation results in an interesting perspective.
Keywords: Griekse oudheid